Establishment of sampling techniques in papaya using the rapid nitrate test - Tantung, R. L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1996)
Using the rapid nitrate test, sampling techniques in papaya were established. The recently mature leaves gave the highest nitrate concentration when sampled at 9:30 AM. Petiole sap NO-N concentration was higher at the vegetative stage (4 1/2 mos old) compared to reproductive stage (6 1/2 mos old).